Potentialities and usage of Internet communications: A qualitative and quantitative overview. - Domenico Campisi; Carlo Tesauro (European Regional Science Association (ERSA), 1998)
Technological innovation is the main responsible of the phenomenon called Internet. This innovative use of the medium accomplishes those concepts and dreams of science fiction's authors. Nevertheless, the new potentialities supplied by this new medium have only partially been analysed until today. Our purpose is to define a qualitative schema to investigate the main usage of Internet potentialities, joined with a quantitative analysis in the main geographic areas paying a special attention to the national and EEC data. The first goal is pursued identifying the better usage of the medium done by some representitives of the main socio-economic categories. These representitives could be chosen in any geographic area and their performances will be investigated, compared and used to define an analysing schema. The second objective is obtained using the best so-called "search engines", since the main characteristic of a site is represented by it's accessibility. Moreover, some cross-section data will be provided to enhance some more meaningful insights.
Keywords: 330